2022
DOI: 10.1111/1759-7714.14578
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical results between high grade patterns in stage I lung adenocarcinoma

Abstract: Background: The histological subtype has been introduced in invasive lung adenocarcinoma. The predominant micropapillary and solid subtypes are categorized as high-grade patterns and provide a worse prognosis. However, the prognostic analysis of high-grade patterns has not previously been fully investigated. Thus, this study aimed to investigate the prognostic role of high-grade patterns in pathological stage I lung adenocarcinoma. Methods: Patients with stage I lung adenocarcinoma and micropapillary or solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…It allows prognostic stratification in terms of overall survival (OS) and recurrence‐free survival (RFS) in all cancer stages, as well as in the subgroup of stage I patients. Additionally, IASLC grade 3 has been identified as the most relevant risk factor for predicting clinical outcomes 9,10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It allows prognostic stratification in terms of overall survival (OS) and recurrence‐free survival (RFS) in all cancer stages, as well as in the subgroup of stage I patients. Additionally, IASLC grade 3 has been identified as the most relevant risk factor for predicting clinical outcomes 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, IASLC grade 3 has been identified as the most relevant risk factor for predicting clinical outcomes. 9,10 As intraoperative biopsy results are often inconclusive, more extensive pulmonary resection or lymph node dissection may be required to avoid the need for additional surgery. Several studies have reported preoperative clinical and radiological variables that are predictive factors for micropapillary, solid pattern, and IASLC grade 3 cancer.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Recently, it has been reported that patients with MP have a high postoperative recurrence rate and poor overall survival (OS). [2][3][4][5] As for the type of recurrence, lymph node metastasis was more likely in lung adenocarcinoma patients with MP. 6,7 Nitadori et al also reported that local recurrence was more common in patients with MP after partial resection and that MP might spread within the lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Lung adenocarcinoma is the major histological type of lung cancer and is further classified into five subtypes: lepidic, acinar, papillary, solid, and micropapillary. Solid and micropapillary patterns are subtypes considered to have a poor prognosis and have been reported to have a high postoperative recurrence rate 1–8 . However, the current TNM classification does not reflect these factors, and treatment according to histological subtype has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Jeon et al compared the clinicopathological features and clinical course of patients with the MPA and SPA subtypes, including predominant and non-predominant subtypes after curative resection of stage I lung adenocarcinoma and analyzed the prognostic factors. The clinical results were different for stage I high-grade adenocarcinoma and the predominant micropapillary subtype was an independent prognostic factor for recurrence, whereas the solid subtype was a signi cant factor for overall survival [7].…”
Section: Introductionmentioning
confidence: 87%